Is synchronous online learning more beneficial than asynchronous online learning in a Saudi EFL setting: teachers’ perspectives - Alfares, Nurah (Frontiers in Education, 2024)
This research investigates the English as a foreign language (EFL) teachers’ perception of the pros and cons of synchronous and asynchronous online learning for EFL students in Saudi Arabia. 121 EFL teachers from public schools in different regions participated in this study. A questionnaire has been used to collect this study’s main data and distributed it online to all EFL teachers in Saudi Arabia. After the statistical analysis of data, the study’s main findings revealed that the advantages of synchronous learning are helping learners reduce space barriers and saving time for learners. However, the main disadvantages of synchronous learning are the disruption of the internet: slow speed, the miscommunication of learners and getting bored through learning. The main findings for the advantages of asynchronous learning are the chances for learners to replay the lesson many times, the opportunities for learners to have more time for thinking, and the opportunities for learners to enhance autonomy and self-regulated learning. However, the disadvantages perceived by the participants were that asynchronous learning requires more responsibilities from learners in self-controlling, self-motivation, and autonomous learning skills. This study is one of the few studies investigating and comparing EFL teachers’ perceptions of synchronous and asynchronous online learning. Therefore, this research could serve the Ministry of Education by exploring the challenges that instructors face in teaching and highlighting the advantages of online teaching to increase awareness among Saudi teachers of its essential role in EFL learning.